Conclusion (Scottish Historical and Archaeological Internet Reports, 2007)
Funerary rites the world over confirm relationships between the living, and establish a different relationship with the newly dead. These relationships may not end with the burial, but continue long after in dialogues with the ancestors, in physical or incorporeal form. Rites of placation or supplication and rituals of remembrance may all have a part to play.